The Effectiveness of Rehabilitation as an Effort to Address Narcotics Issues - Rahmah, Siti Rahmah; Beridiansyah, Beridiansyah; Hafni, Irma; Jubir, Jubir; Fajri, Nur (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2024)
Rehabilitation of drug addicts serves as a form of social protection, aiming to reintegrate individuals into society and reduce relapse. This normative and descriptive legal research evaluates the effectiveness of rehabilitation in addressing drug abuse, especially in Aceh. The study identifies key success factors such as community and government support, holistic rehabilitation approaches, and robust post-rehabilitation programs. Challenges include limited facilities, stigma, and ineffective reintegration. The research concludes with recommendations to improve rehabilitation effectiveness through infrastructure development, education, inter-agency collaboration, and enhanced aftercare services.